Modelagem constitutiva da fadiga em ligas com memória de forma - Dornelas, Vanderson Marcio (2020)
This contribution presents a new macroscopic three-dimensional constitutive model to describe functional and structural fatigue on shape memory alloys considering a continuum damage perspective. Classical plasticity and transformation induced plasticity are incorporated into the model to allow the description of the main aspects of the thermomechanical behavior of SMAs. An equivalent critical damage is proposed to define the fatigue life of SMAs, considering different behaviors of martensitic and austenitic phases. The proposed model is based on experimental tests that allowed to evaluate the main macroscopic aspects of the thermomechanical behavior of SMAs. Numerical simulations are compared with experimental data showing the capabilities of the proposed model. Results show that the model responses are in close agreement with experimental data. In addition, general numerical simulations are presented in order to explore the general thermomechanical behavior of shape memory alloys, showing the model's ability to describe a wide variety of phenomena.